Rancang Bangun Aplikasi untuk Analisis Tingkat Kepuasan Mahasiswa Terhadap Pelayanan Akademis AMIK Imelda Medan dengan Menggunakan Algoritma Servqual - Manalu, Mamed Rofendi; Siringoringo, Rimmar (LPPM UNIKA Santo Thomas, 2020)
AMIK IMELDA is one of the campuses that foster students at the diploma three or academic level with several majors and consistently serves students both in terms of teaching and administrative services, to ensure that the service process is well delivered to every important component in the institution in providing the best for students because students are part of the campus that cannot be separated from the activities in the AMIK IMELDA environment, but until now there has been no analysis process to ensure the level of service in the AMIK IMELDA environment. In measuring the level of academic service at Amik Imelda using the SERVQUAL approach where the process is used to measure the service quality of the attributes of each dimension, so that a gap value will be obtained which is the difference between consumer perceptions, in this case, students towards the services that have been received. with the hope of being accepted. The measurement of this method is by measuring the service quality of the attributes of each dimension, so that the value of the gap will be obtained which is the difference between consumer perceptions of the service received and consumer expectations of the service to be received. The purpose of this study is to analyze the level of satisfaction with academic services by all academic communities in the AMIK IMELDA Medan environment with several assessment factors for services that refer to reliability, namely the ability to implement in a timely and reliable manner, responsive to the readiness of all environmental elements in providing service quickly and responsively, Assurance, namely the ability of staff to know the right service, quality of hospitality, attention and courtesy in providing services, skills in providing information, Emphaty, namely individual attention given to students by the Institution and the last is Tangible, covering appearance of physical facilities, such as the front office building, parking available, cleanliness, tidiness and comfort of the room, complete communication equipment and appearance. This type of research is product development by following the process of data collection, problem analysis, application of the chosen method and continued with application design up to the testing stage. This research is a research of SKIM PDP (Beginner Lecturer Research) which is included in the basic research category with TKT 1-3 sizes, the target outcome in the study is the main target of publication in accredited national journals with additional isBN books and registered with Haki